2022
DOI: 10.1038/s41467-022-34947-6
|View full text |Cite
|
Sign up to set email alerts
|

U.S. winter wheat yield loss attributed to compound hot-dry-windy events

Abstract: Climate extremes cause significant winter wheat yield loss and can cause much greater impacts than single extremes in isolation when multiple extremes occur simultaneously. Here we show that compound hot-dry-windy events (HDW) significantly increased in the U.S. Great Plains from 1982 to 2020. These HDW events were the most impactful drivers for wheat yield loss, accounting for a 4% yield reduction per 10 h of HDW during heading to maturity. Current HDW trends are associated with yield reduction rates of up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 55 publications
0
14
0
1
Order By: Relevance
“…Also, multiple limitations may occur at the same time. As an example of this phenomenon, Zhao et al. (2022) attributed considerable losses of winter wheat to the co-occurring extreme events of high temperatures, dryness and hard winds compared to events in which a single limiting factor occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Also, multiple limitations may occur at the same time. As an example of this phenomenon, Zhao et al. (2022) attributed considerable losses of winter wheat to the co-occurring extreme events of high temperatures, dryness and hard winds compared to events in which a single limiting factor occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Recent efforts evaluated probabilistic patterns of drought (Sciarresi et al, 2019) and of the combination of drought and thermal regime stresses (Couëdel et al, 2021;Lollato et al, 2017Lollato et al, , 2020Zhao et al, 2022) for winter wheat in the US Great Plains, overwhelmingly concluding that grain yield of winter wheat in this region is often impacted by heat and drought stresses. The current research expands on these previous environmental characterizations to explore functional relationships between weather experienced in the growing season and grain yield and quality traits.…”
Section: Environmentmentioning
confidence: 99%
“…In part, because wheat stubble provides excellent soil cover to minimize wind and water erosion and improve soil water storage in the central Great Plains, contributing to soil water conservation needed for successive crops (Schlegel et al., 2023). However, a recent study reported that the frequency of hot‐dry‐windy weather events has increased in Kansas and surrounding regions and is attributed to significant yield reduction (Zaho et al., 2022). Schlegel et al.…”
Section: Introductionmentioning
confidence: 99%